Investigating sustainability challenges for the National Health Insurance Fund in Tanzania: a modelling approach - Günther Fink; Fabrizio Tediosi; August Kuwawenaruwa; Brianna Osetinsky (BMJ Open, 2023)
Objective This study aimed to model the long-term cost associated with expanding public health insurance coverage in Tanzania.Design, setting and participants We analysed the 2016 claims of 2 923 524 beneficiaries of the National Health Insurance Fund in Tanzania. The analysis focused on determining the average cost per beneficiary across 5-year age groups separated by gender, and grouped by broad health condition categories. We then modelled three different insurance coverage scenarios from 2020 to 2050 and we estimated the associated costs.Outcome measures Average cost per beneficiary and the projected financing requirements, projected from 2020 to 2050.Results The analysis revealed that the average per beneficiary cost for insurance claims was $38.58. Among males over 75 years, the average insurance claims costs were highest, amounting to $125. The total estimated annual cost of claims in 2020 was $151 million. Under the status quo coverage scenario, total claims were projected to increase to $415 million by 2050. Increasing coverage from 7% to 50% would result in an additional financing requirement of $2.27 billion. If coverage would increase by 10% annually, reaching 56% of the population by 2050, the additional financing need would amount to $2.84 billion.Conclusion This study highlights the critical importance of assessing the long-term financial viability of health insurance schemes aimed to cover large segments of the population in low-income countries. The findings demonstrate that even without expansion of coverage, financing requirements for insurance will more than triple by 2050. Furthermore, increasing coverage is likely to substantially escalate the cost of claims, potentially requiring significant government or external contributions to finance these additional costs. Policymakers and stakeholders should carefully evaluate the sustainability of insurance schemes to ensure adequate financial support for expanding coverage and improving healthcare access in low-income settings.